The use of colonic and anorectal high‐resolution manometry and its place in clinical work and in research. Issue 12 (30th July 2015) - Dinning, P. G.; Carrington, E. V.; Scott, S. M.
Abstract: Background: In the esophagus, high‐resolution manometry (HRM) has become a standard diagnostic tool in the investigation of suspected motility disorders. However, at the opposite end of the digestive tract (i.e., the colon and anorectum), the use of HRM still remains in its infancy, with relatively few published studies in the scientific literature. Further, the clinical utility of those studies that have been performed is largely undetermined. Purpose: This review assesses all of the HRM studies published to date from both the colon and anorectum, explores the catheter types used, and attempts to determine the worth of HRM over traditional 'low‐resolution' recordings from the same regions. Ultimately, this review addresses whether HRM currently provides information that will benefit patient diagnosis and treatment. Abstract : This review summarizes the findings from all high‐resolution manometry studies in the anorectum and colon, and indicates future directions for this field.